Efektifitas Penerapan Absensi Elektronik Dalam Meningkatkan Disiplin Pegawai (Studi Kasus Sala Satu Universitas Di Kota Ternate) - Fifi Freidah; Abd. Wahab Hasyim; Fadhliah M. Alhadar (Universitas 45 Surabaya, 2023)
The purpose of this study is to determine the effectiveness of electronic attendance in improving employee discipline and the application of attendance in improving employee discipline. The type of research used is descriptive with qualitative methods. Data collection techniques in this study are observation, interviews and documentation. Data sources were obtained using purposive sampling and accidental sampling techniques. Data analysis used in this study is interactive data analysis consisting of several components, namely data collection, data reduction, data presentation and conclusions. The results in this study show that the effectiveness of electronic attendance in improving employee discipline has been very good. And the application of Electronic Attendance Id Card to improve discipline is very good. This shows that with the implementation of employee discipline rules, employees obey applicable regulations such as delay, there are sanctions that must be carried out, namely salary deductions so that employees can carry out their duties properly and the level of employee discipline is increasing.